La ricezione produttiva contemporanea di Hölderlin: La performance poetico-biografica di Andrea Balzola (2012) e il film sperimentale «Hyperion» di Maria Giovanna Cicciari (2014) (Studia theodisca, 2017)
This article examines Andrea Balzola’s cross-media performance Le voci del vulcano (2012), which is a computer based interactive video installation dedicated to Friedrich Hölderlin, and Maria Giovanna Cicciari’s Hyperion (2014), an experimental film inspired by the name-sake German novel, as exemplary documents of the productive reception of Hölderlin’s life and work in Italy today.